LATENCY AND AMPLITUDE OF HAND REFLEX IN THE ACTIVE SPORTSMEN - Serpil Bulut,; Recep Özmerdivenli,; Ayhan Kamanlı,; Tahir Kurtuluş Yoldaş,; Kürşat Karacabey Cemal Gündoğdu, (Archives of Rheumatology, 2000)
The evaluation of proximal segments using classical electrophysiological methods for nerve conduction velocities is not sufficient. In this study, the effects of regular exercise on H-reflex and T-refiex amplitude and latency was investigated. H-reflex and T-reflex amplitude and latency values of 20 subjects (test group, 10 football player, and 10 volleyball player) who nave been regularly exercising for 8.73±4.45 years and 20 students (control group) who have not been regularly exercised were measured. The H-reflex amplitude and latency values of test and control group were 3.71 ±1.6 mV and 27.98±2.16 ms; 6.83±2.23 mV and 27.69±2.0 msec, respectively. There was no statistically difference betvveen the two groups in relation with H-reflex latencies (p>0.05). The amplitude of H-reflex was significantly higher in the control group (p<0.05). The T-reflex amplitude and latency values of test and control groups were 3.78±1.99 mV and 32.08±2.04 ms; 4.31 ±1.43 mV and 31.52±2.27 msec, respectively. Despite the amplitude of T-reflex was higher in the control group, the difference between the two groups with respect to amplitude and latency was not significantly different (P>0.05). There was no signı'ficant difference betvveen volleyball and football players vvith respect to H and T-reflex amplitude and latency. In conclusion, the H-reflex amplitude recorded from trained muscle was significantly low and this could be due to lower number of motor neurones stimulated by type la fibers. This may be due to less efficency of type la excitatory afferents on motor interneurones in trained subjects. Therefore, the level of exercise should be considered as an influencing parameter when evaluating the amplitude of H and T reflexes.